The Abundance of Birds in Uganda’s inhabited Areas and the Importance of Pastoral Areas - Asasira, J.; Pomeroy, D. (African Journal of Ecology, 2008)
The Uganda bird-monitoring programme has so far generated more than 18,600 observations from the 37 sites where land birds are monitored annually. Ten of the sites are in farmed area (agroecosystems), thirteen in semi-natural pastoral ecosystems and fourteen in natural ecosystems (mainly national parks). The farms are almost entirely small-scale and very diverse in their land use systems. Monitoring is by Timed Species Counts from which the frequency of recording of each species at each site can be generated (with over 460 species recorded so far, the overall spread sheet contains many zero values). The species numbers overall were the highest at natural sites (375 species), which also had the highest numbers of birds that often use trees, and those which are specialist grassland or aerial species or Palearctic visitors; but numbers of Red Data species are the highest in semi-natural sites. As one would expect, formerly forested areas and moist savannas support most tree birds, whilst Red Data species were most frequently recorded in areas of impeded drainage – typically, these are periodically flooded. Grassland specialists are more common in dry than in moist savannas. Palearctic migrants are nowhere common. Uganda’s pastoral areas, on which domestic livestock graze and browse on predominant natural vegetation, are rich in birds and deserve a much more detailed study.
Keywords: birds; pastoral areas